Motorcyclists’ Prolonged Riding Simulation: The Setup and Procedures / Helmi Rashid ... [et al.] - Rashid, Helmi; Omar, Abdul Rahman; Ahmad, Ismail Nasiruddin; Mohamed, Zulkifli; Wan Fauzi, Wan Muhammad Syahmi; Mahmud, Zamalia; Haron, Rohani (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
This study focuses on pilot testing and simulation setup of motorcyclists’ prolonged riding activity using an indoor motorcycle simulator facility (Postura MotergoTM) that was developed by a group of researchers from the Motorcycle Engineering Technology Laboratory (METAL) at the Faculty of Mechanical Engineering, Universiti Teknologi MARA, Malaysia. The facility is amongst the many motorcycle simulators available all around the world but with several special additional features that makes this facility to be the first of its kind. Five (5) healthy male respondents age of 23 were involved in this pilot testing that required them to ride the motorcycle simulator for a maximum of two hours non-stop. The riding environment replicated near-to-real motorcycle riding experience that includes the motorcycle, control system, visual display, sounds, vibrations, motion and windblast. The environments’ simulation setups were monitored using digital electronic and scientific devices to make sure that the setup is within the allowable safety range being permitted. Meanwhile, the respondents’ muscle activities were also monitored using a wireless surface electromyography (sEMG) device to observe for any signs of muscle fatigue during the non-stop prolonged riding simulation. Findings from this study highlighted new issues on the significant muscle groups being observed that may contribute to motorcyclists’ muscle fatigue during prolonged riding and also several setup requirements. The outputs of this study are hoped to be a reference platform for further indoor motorcycle simulation activities in the near future.